(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Despite the high level of awareness about the importance of post-operative pain management, lot of investigations and study results show an unacceptable high rate of incidence of pain after surgery. Pre- emptive pain control is regional or systemic analgesics, applied before starting the surgical procedure. The effect is achieved by suppressing, central or peripheral nociceptors, either together or separately by sensitization. We studied the effect of intravenous Paracetamol as pre-emptive analgesic in patients undergoing laparoscopic cholecystectomy. Method: A total number of 60 adult patient with ASA physical status I & II scheduled for Laparoscopic cholecystectomy under general anaesthesia were randomly enrolled in this study. Patients were randomly allocacated equally into two groups A and B according to computerized random table, 30 in each group. Patients of Group A (n=30) received I.V Paracetamol 10mg/kg(100ml) 10 min before skin incision and Group B (n=30) received 100 ml of Normal saline 10 min before skin incision. It was a single blind, randomized, prospective, case-control study. Observation and management of pain, nausea, vomiting, respiratory depression, allergic reaction, amount of opioid requirement and time of analgesic demand after operation were carried out in data collection sheet. Result: The total dose of postoperative opioid needed in Group-A was significantly lower than that in the Group- B(p=0.012). The pain scores were comparatively low in case of group-A than that in Group-B from beginning to 24 hours of evaluation following operation(p=0.027). About one-third (32%) of the patient in each group experienced nausea at 1 hour interval post operatively. However, the complaint of nausea at 6 and 12 hours was much less in the Group-A than that in the Group-B. Vomiting was negligible in either group. Majority (80%) of patient in Group-B demanded analgesic (pethedine) 10 minutes earlier after operation as opposed to only 8% of patients in Group-A (p<0.001). No other side effects were recorded in either of the groups. Conclusion: Our findings indicate that pre-emptive administration of iv Paracetamol (10mg/kg) in patients undergoing Laparoscopic Cholecystectomy ensures an effective postoperative analgesia, increases the time to first analgesic requirement and reduces opioid consumption. Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 159-163